Sustainable materials in Malaysia: a systematic review on academic research and application in product design industry - Ismail, Zati Hazira; Liew, Yong Kian; Bahrudin, Fadzli Irwan; Daud, Nuraini (2021)
A more circular economy is necessary to mitigate the current production and consumption system's environmental impacts. One prominent global strategy is to utilise alternative natural and recycled materials to close the loop of biological and technical resources. Such materials are often referred to as environmentally benign materials or sustainable materials. More than a quarter of the research and development expenditures since 2018 are spent implementing sustainable economic development in Malaysia. However, despite government supports for industries to focus on sustainability aspects in their business operations, the case for sustainable materials in product design development is less clear. An overview of the breadth of development and current status of sustainable materials development and commercialisation remains unavailable. This paper presents a systematic review of academic articles and industrial applications of sustainable materials in Malaysia, using the Reporting Standards for Systematic Evidence Syntheses (ROSES) method. The review shows promising sustainable material exploration, and the overall development reflects an early transition to a circular economy. However, greater coordination and concerted efforts are needed as there is a significant gap between academic research and commercial product applications in terms of sustainable material types and product commercialisation.